The influence of a fruit smoothie or cereal and milk breakfast on subsequent dietary intake: a pilot study. (4th July 2019) - McCartney, Danielle; Langston, Keanne; Desbrow, Ben; Khalesi, Saman; Irwin, Christopher
Abstract: Smoothies are popular breakfast foods. This study examined the effect of consuming Cereal & Milk (CM) or a nutritionally-comparable Fruit Smoothie (FS) for breakfast on daily energy intake (EI) in free-living adults and the extent to which individuals compensated for calories ingested in a High Energy Fruit Smoothie (HE). Ten participants (28.4 ± 2.2y; 23.3 ± 1.0 kg·m −2, Mean ± SEM) attended the laboratory on 3 consecutive days per week for 3 weeks. Each week, they received a CM, FS or HE breakfast, then recorded all food/beverages consumed across the remainder of the day. The CM and FS were energy-matched to participants' usual breakfast (1675 ± 283 kJ), while the HE contained an additional 100 kJ·kg −1 of maltodextrin (3019 ± 335 kJ). Mean 3-day EI was similar on CM and FS (7894 ± 547 vs. 7570 ± 463 kJ, p > .05), but elevated on HE (8861 ± 726 kJ, p = .012). Thus, individuals who substitute CM for a FS breakfast should be mindful that energy-dense beverages may result in increased daily EI.